Correlation between Alpha Fetoprotein and Platelet Profile in Hepatocellular Carcinoma - Rahmawati Rahmawati; Agus Alim Abdullah; Ibrahim Abdul Samad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Hematology abnormalities are commonly found in Hepatocellular Carcinoma (HCC) patients. Platelet (PLT) count in HCC can be low, normal or high, and influenced by tumor and liver damage. There are limited studies about the correlationp between AFP and platelet profile of HCC in Indonesia, especially in Makassar. This study is aimed to analyze the correlation between AFP and platelet profile in HCC patients. A retrospective cross-sectional study was carried out from  January 2016 to June 2017 on 231 HCC subjects. The correlation between AFP and platelet profile, the correlation of AFP and platelet profile with the diagnosis were analyzed by Independent t-test and Chi-Square. There was no significant correlation between AFP and PLT profile and no significant correlation between AFP and HCC with and without cirrhosis with p>0.05 and p=0.094, respectively. Platelet count and PCT were significantly lower in cirrhotic HCC ompared to non-cirrhotic HCC (p<0.01, p<0.01, respectively), PDW and MPV were significantly higher in cirrhotic HCC compared to non-cirrhotic HCC  (p<0.05, p<0.05,  respectively). Mean platelet count and PCT in cirrhotic HCC were significantly lower compared to non- cirrhotic HCC, and mean PDW and MPV in cirrhotic HCC c were significantly higher compared to non-cirrhotic HCC. Further research was suggested to evaluate tumor size and nodules of HCC.